What Do Teacher Candidates Know About Large-Scale Assessments? What Should They Know? - Childs, Ruth A.; Lawson, Alexandra (Alberta Journal of Educational Research, 2003)
As states and provinces develop large-scale assessment programs linked to their curricula, teachers are increasingly expected to interpret the assessment results and to explain them to parents. The challenge for teachers is especially great in Ontario, which began developing an assessment program in 1996 after almost three decades without provincially mandated testing. Three hundred and sixty teacher candidates completed a questionnaire on their knowledge about, exposure to, and opinions of the assessments. Many teacher candidates held strong views, often negative, about the assessments. Even those who had little exposure to or knowledge of the assessments held predominantly negative opinions.